Spiders - Marsh, Laura F. (Washington, DC : National Geographic, 2011)
An introduction to spiders.
It's a spider! -- Spiders, spiders everywhere! -- A spider's body -- Spider food -- Senses -- Web builders -- Spinning silk -- Super spiders! -- Baby spiders -- Helpful spiders -- What in the world?
b
b
Keywords: Spiders -- Juvenile literature